2016
DOI: 10.1159/000445007
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Pancreatic Disease - Current Status

Abstract: Laparoscopic procedures have advanced to represent the new gold standard in many surgical fields. Although application in pancreatic surgery is hampered by the friable nature of the gland and the difficulty of its exposure, advanced technology and surgeons' experience are leading to an expansion of minimally invasive pancreatic surgery. Addressing the whole range of main operative procedures, this review analyzes the literature data so far to give an overview about the current status of minimally invasive panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 75 publications
0
11
0
2
Order By: Relevance
“…The laparoscopic approach is associated with a lower incidence of new onset organ failure post-operatively when compared to the open approach [ 47 , 48 ]. The currently used technique is laparoscopic necrosectomy, using a retrogastric transmesocolic or retroperitoneal approach to the lesser sac [ 49 ]. Another alternative after the placement of the percutaneous drain would be a videoscopic-assisted retroperitoneal debridement (VARD), where a small 5 cm subcostal incision is made to allow larger pieces of solid debris to be removed.…”
Section: Necrotizing Pancreatitis: Management and Treatmentmentioning
confidence: 99%
“…The laparoscopic approach is associated with a lower incidence of new onset organ failure post-operatively when compared to the open approach [ 47 , 48 ]. The currently used technique is laparoscopic necrosectomy, using a retrogastric transmesocolic or retroperitoneal approach to the lesser sac [ 49 ]. Another alternative after the placement of the percutaneous drain would be a videoscopic-assisted retroperitoneal debridement (VARD), where a small 5 cm subcostal incision is made to allow larger pieces of solid debris to be removed.…”
Section: Necrotizing Pancreatitis: Management and Treatmentmentioning
confidence: 99%
“…Laparoscopic pancreatoduodenectomy (LPD) is emerging as a safe and effective option compared to open pancreatoduodenectomy (OPD), but still remains an area of significant controversy [14]. Several retrospective studies have shown LPD to be non-inferior in regards to morbidity and mortality when compared to OPD [512].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional approach to the treatment of IPN had historically been open necrosectomy (ON) with the complete removal of the infected tissue. Nevertheless, due to the still high rates of complications and death characterizing the ON, in the last decade, it has been gradually replaced by minimally invasive procedures that seem to reduce the incidence of postoperative new-onset organ failure compared with the open procedures [ 12 , 13 , 16 18 ]. Less invasive procedures, indeed, have been successfully proposed and tested, such as percutaneous drainage (PD), endoscopic transgastric necrosectomy (ETN), or video-assisted retroperitoneal debridement (VARD) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%